The effect of replacing red algae on histomorphology and enzymes of digestive tract of Nile tilapia, Oreochromis niloticus - Sanaz Kord; Rahim Abdi; Isaac Zamani; Rhima Peyghan (تغذیه آبزیان)
Introduction: Nile tilapia, Oreochromis niloticus is one of the commercially important fish species in many parts of the world. Red algae constitute a widely-used composition of the diet. The purpose of the present study was to replace the red algae on the diet with enzymes and its impact on Nile tilapia gastrointestinal tract. Materials and methods: A total of 120 pieces of tilapia with an average weight of 30 ± 1 g after acclimation for 6 weeks in 100-L aquariums were divided in 4 groups and three replicates (10 fish in each tank) and then fed with basic diet (BioMar Company, France) containing zero, 3%, 6%, and 9% red algae (C, T3%, T6% and T9%). At the end of the rearing period, the fish was anesthetized by clove powder and after dissecting the abdomen, a  0.5-cm tissue samples were removed from the middle of the esophagus, as well as the anterior, middle, and posterior parts of the intestine, then placed in 10% neutral buffered formalin as a fixative solution. After going through the routine steps of tissue preparation, including dehydration with alcohol, clarification with xylol, blocking with paraffin, cutting with a thickness of 4-6 microns with a microtome, and hematoxylin-eosin staining, finally, the evaluation was done with a light microscope. Results: Histological examination in the mid-esophagus, anterior, middle, and posterior parts of the intestine showed that the highest number of mucous cells, the highest thickness of the epithelium and muscle layer, as well as the highest height and thickness of the esophageal villi were observed in the group receiving the diet containing 9% red algae. Also, protease, amylase and lipase enzymes in the treatments had a higher level than in the control group, with the exception that the amount of protease was higher than amylase and lipase. Conclusion: According to the results of the present study, it can be concluded that using red algae in the diet of Nile tilapia exhibited no side effects at the aforementioned levels, even improved tissue metric parameters.